2019
DOI: 10.3390/ma12193135
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative 3D Finite Element Computational Study of Three Connections

Abstract: Masticatory overload on dental implants is one of the causes of marginal bone resorption. The implant–abutment connection (IAC) design plays a critical role in the quality of the stress distribution, and, over the years, different designs were proposed. This study aimed to assess the mechanical behavior of three different types of IAC using a finite element model (FEM) analysis. Three types of two-piece implants were designed: two internal conical connection designs (models A and B) and one internal flat-to-fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
2
9
0
2
Order By: Relevance
“…In general, different abutment types have no effect on stress distribution at the supporting bone, both in cortical and cancellous, which is in agreement with several studies that found no significant differences of stress distribution in supporting bone between the different abutment materials, abutment configurations, and restorative crown materials 10,34–37 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In general, different abutment types have no effect on stress distribution at the supporting bone, both in cortical and cancellous, which is in agreement with several studies that found no significant differences of stress distribution in supporting bone between the different abutment materials, abutment configurations, and restorative crown materials 10,34–37 …”
Section: Discussionsupporting
confidence: 89%
“…18,32,33 In general, different abutment types have no effect on stress distribution at the supporting bone, both in cortical and cancellous, which is in agreement with several studies that found no significant differences of stress distribution in supporting bone between the different abutment materials, abutment configurations, and restorative crown materials. 10,[34][35][36][37] By comparing the Ti and Zir-TiBase groups, the Ti-base in the Zir-TiBase played an important role in getting better stress distribution at implant than Ti, especially at the implant shoulder region. Titanium has an elastic modulus approximately two times lower than zirconia.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, finite element analysis (FEA) may also contribute to a better definition of the influence of loading variation. For instance, FEA has been applied to investigate the influence on stress of the prosthetic designs associated with implants of varying lengths and distribution [ 104 ], of the prosthetic screw design [ 105 ], or of the distribution of occlusal contacts [ 106 ]. Another area that should be investigated concerns the extent to which the resolution of occlusal overload could be effective in limiting the progression of prosthetically triggered peri-implant bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays it is known how superstructure misfit may result in strain and distortion of its parts, with several complications in both biological and mechanical aspects of the rehabilitation. Concerning the mechanical ones, the most commonly reported are screw loosening, fracture of the prosthetic or implant components [5][6][7][8][9][10][11][12] and prosthetic mainframe damage [12][13][14][15]. Among the biological complications, instead, loss of osseointegration [16] should be considered.…”
Section: Introductionmentioning
confidence: 99%